2020
DOI: 10.1002/mrm.28337
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐heart, ungated, free‐breathing, cardiac‐phase‐resolved myocardial perfusion MRI by using Continuous Radial Interleaved simultaneous Multi‐slice acquisitions at sPoiled steady‐state (CRIMP)

Abstract: Purpose To develop a whole‐heart, free‐breathing, non‐electrocardiograph (ECG)‐gated, cardiac‐phase‐resolved myocardial perfusion MRI framework (CRIMP; Continuous Radial Interleaved simultaneous Multi‐slice acquisitions at sPoiled steady‐state) and test its quantification feasibility. Methods CRIMP used interleaved radial simultaneous multi‐slice (SMS) slice groups to cover the whole heart in 9 or 12 short‐axis slices. The sequence continuously acquired data without magnetization preparation, ECG gating or bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 56 publications
(122 reference statements)
1
31
0
Order By: Relevance
“…Recent studies using Cartesian and radial imaging at 3T have either demonstrated lower spatial-temporal resolution or more limited spatial coverage than what is feasible using spiral trajectories. [19][20][21] The enhanced spatial resolution may increase the ability to assess transmural differences in myocardial perfusion, [24][25][26] and the whole-heart coverage may improve the ability to assess the extent of ischemia and quantify the ischemic burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies using Cartesian and radial imaging at 3T have either demonstrated lower spatial-temporal resolution or more limited spatial coverage than what is feasible using spiral trajectories. [19][20][21] The enhanced spatial resolution may increase the ability to assess transmural differences in myocardial perfusion, [24][25][26] and the whole-heart coverage may improve the ability to assess the extent of ischemia and quantify the ischemic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Recent radial and Cartesian perfusion studies at 3T have used an in-plane resolution of around 1.5-2 mm. [19][20][21][22][23] However, with higher spatial resolution there is increased ability to detect transmural perfusion differences between the epicardium and the endocardium, which could improve the ability to detecting obstructive CAD as demonstrated in prior studies. [24][25][26][27] Recent advance in high-resolution SMS Cartesian perfusion imaging using balanced steady-state free precession (bSSFP) provides another possibility for high-resolution perfusion imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Multiple studies have explored the use of SMS imaging in CMR for faster coverage. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] In particular, SMS acceleration has been used for myocardial T 1 mapping, 13,18 for cine imaging, 16,21 and for perfusion imaging 11,14,15,17,22 using both Cartesian and non-Cartesian acquisitions at different acceleration rates. However, due to coil geometry limitations, SMS acceleration remains limited for CMR, especially in conjunction with in-plane parallel imaging, in which leakage artifacts and noise amplification are observed at high acceleration rates, 23 necessitating improvements in reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous multislice imaging is typically coupled with controlled aliasing, to further increase dissimilarities among the coil profiles across the slices and to reduce g‐factor noise amplification 8 . Multiple studies have explored the use of SMS imaging in CMR for faster coverage 9‐22 . In particular, SMS acceleration has been used for myocardial T 1 mapping, 13,18 for cine imaging, 16,21 and for perfusion imaging 11,14,15,17,22 using both Cartesian and non‐Cartesian acquisitions at different acceleration rates.…”
Section: Introductionmentioning
confidence: 99%